Handbook of Optical Constants of Solids, Five-Volume Set : Handbook of Thermo-Optic Coefficients of Optical Materials with Applications. - Palik, Edward D. (Elsevier Science, 1997)
This set of five volumes, four volumes edited by Edward D. Palik and a volume by Gorachand Ghosh, is a unique resource for any science and technology library. It provides materials researchers and optical device designers with reference facts in a context not available anywhere else. The singular functionality of the set derives from the unique format for the three core volumes that comprise the Handbook of Optical Constants of Solids. The Handbook satisfies several essential needs: first, it affords the most comprehensive database of the refractive index and extinction (or loss) coefficient o.